Multiculturalism in Korean way: the difficulties of the alternative Mass Media Organizations - Ем, Н. Б. (Journal of Oriental Studies, 2017)
The South Korea deserves special attention to discussion of the multiculturalism because it is considered as the most ethnically homogeneous country in the world. In spite of the Korean Mass Media, governmental channels release many programs the basic character of which is the stereotype of the compassion and pity to migrant workers .That causes the displeasure and the desire to show migrant workers as members of the Korean society who invest huge contribution to Korea. The author considers that Mass Media created by the migrant workers is instrument that connects the Korean society and migrant workers. The limitations in considered materials gives new directions for the further research of migrants as a whole and marital migrants as a part of this formation.